Revefenacin, a Long‐Acting Muscarinic Antagonist, Does Not Prolong QT Interval in Healthy Subjects: Results of a Placebo‐ and Positive‐Controlled Thorough QT Study. Issue 1 (29th August 2019) - Borin, Marie T.; Barnes, Chris N.; Darpo, Borje; Pendyala, Srikanth; Xue, Hongqi; Bourdet, David L.
Abstract: Revefenacin is a novel once‐daily, lung‐selective, long‐acting muscarinic antagonist developed as a nebulized inhalation solution for the maintenance treatment of chronic obstructive pulmonary disease. In a randomized, 4‐way crossover study, healthy subjects received a single inhaled dose of revefenacin 175 µg (therapeutic dose), revefenacin 700 µg (supratherapeutic dose), and placebo via standard jet nebulizer, and a single oral dose of moxifloxacin 400 mg (open‐label) in separate treatment periods. Electrocardiograms were recorded, and pharmacokinetic samples were collected serially after dosing. The primary end point was the placebo‐corrected change from baseline QT interval corrected for heart rate using Fridericia's formula, analyzed at each postdose time. Concentration‐QTc modeling was also performed. Following administration of revefenacin 175  and 700 µg, placebo‐corrected change from baseline QTcF (ΔΔQTcF) values were close to 0 at all times, with the largest mean ΔΔQTcF of 1.0 millisecond (95% confidence interval [CI], −1.2 to 3.1 milliseconds) 8 hours postdose and 1.0 millisecond (95%CI, −1.1 to 3.1 milliseconds) 1 hour postdose after inhalation of revefenacin 175 and 700 µg, respectively. Revefenacin did not have a clinically meaningful effect on heart rate (within ±5 beats per minute of placebo), or PR and QRS intervals (within ±3 and ±1 milliseconds of placebo, respectively). Using concentration‐QTc modeling, an effect of revefenacin > 10 milliseconds can be excluded within the observed plasma concentration range of up to ≈3 ng/mL. Both doses of revefenacin were well tolerated. These results demonstrate that revefenacin does not prolong the QT interval.